RELASI AGAMA DAN SAINS PANDANGAN IAN G. BARBOUR (KONFLIK, INDEPENDEN, DIALOG, DAN INTEGRASI) - Muhammad Saupiyani (PT. Saha Kreasi Indonesia, 2025)
This article aims to explain four models of the relationship between religion and science as proposed by Ian G. Barbour: conflict, independence, dialogue, and integration. This research approach uses a literature study method by compiling various sources of literature such as books, journals, and relevant research findings as references. The study results show that the relationship between religion and science is not always contradictory; the conflict model illustrates sharp differences between the two, the independence model emphasizes the separation of domains, the dialogue model opens space for communication and cooperation, while the integration model combines both into a harmonious unity. Based on this analysis, it can be concluded that the ideal relationship between religion and science is dialogical and integrative. Their collaboration will produce knowledge that is not only intellectually advanced but also grounded in moral and spiritual values, thereby shaping human civilization.